Strategi Pengelolaan dan Pertahanan Wilyaha Perbatasan Udara Republik Indonesia: Tantangan Aspek Politik, Yuridis, dan Operasional - Makaariim, Mufti (UI Scholars Hub, 2009)
This article is written in order to answer an issue management and defense in Indonesian air territory. Nowadays, we need to build management strategy and defense system to dealing with threat in the decent manner. Defense system in territory is less adequate compared to defense system at land and sea. Thus, every obstacles starting from political level and legislation must be our concern. Defense system in the air territory must also be our future priority regarding the use of natural resources for the benefit of Indonesian people.